Airportness the nature of flight - Schaberg, Christopher (Bloomsbury Academic, 2017)
"The term "airportness" has been used to describe the architectural feel of modern terminals and concourses.In his third book about airports, Christopher Schaberg argues that airportness is not just a way of thinking about design, but also the feelings and sensations related to everyday patterns of flight. It is seeing planes in the sky, recognizing vague roars from above, and interpreting the routines of air travel-from sliding doors, to jet bridge, to lavatory. Airportness: The Nature of Flight departs from where The End of Airports left off, speculating about the future of flight and contemplating aircraft as they appear in a variety of contexts. Airportness explores how planes have become surprisingly natural objects: experienced as unquestionable set pieces, props, and passages--airportness is the rumbling background noise of the jet age."